From 2D to 1D functionalization: Steps towards a carbon nanotube based biomembrane sensor for curvature sensitive proteins (Phys. Status Solidi A 6∕2015). Issue 6 (June 2015) - Ostermaier, Frieder; Scharfenberg, Linda; Schneider, Kristian; Hennig, Stefan; Ostermann, Kai; Posseckardt, Juliane; Rödel, Gerhard; Mertig, Michael
<x xml:space="preserve">Abstract</x> Membrane proteins are not homogeneously distributed throughout the membrane. One proposed localization mechanism is related to the membrane curvature. Defects in lipid bilayers can create hydrophobic sites at the bilayer surface – this promotes a selforganization of proteins with hydrophobic motifs in areas of high defectivity, i.e. high curvature. In the work by Ostermaier et al. (pp. 1389–1394), single‐walled carbon nanotubes (SWCNT) are used to create defects by bending a supported lipid bilayer (SLB) as shown on the cover top left. This mechanism is used to build a sensor platform with localized, one‐dimensional trapping areas for proteins along SWCNTs. The build‐up of the sensor platform involves three steps of self‐assembly. First, SWCNT are deposited by dielectrophoresis. This creates a mostly parallel network of SWCNT. Next, a supported lipid bilayer is formed by rupture of liposomes. Third, proteins diffusing in the SLB become localized in the curved vicinity of carbon nanotubes by self‐organization. The specific binding of curvature‐sensitive proteins to the bent areas of the membrane is investigated by fluorescence microscopy as shown in the background of the cover. The use of a cystein group at the end of the hydrophobic motif also allows to exchange the fluorescent group with different functional groups.